Language Feasibility in Students' Textbooks Grade 1 Elementary School - Budiono, Nugroho Bagus (Elementary Education Journal, 2024)
Background: This study evaluates the language feasibility of the Grade 1 student textbook on the theme Kegemaranku (My Favorites) from the 2013 Curriculum published by the Ministry of Education and Culture, focusing on its conformity to students' developmental levels, communicative effectiveness, and the coherence of its content structure. Method: A qualitative descriptive approach with content analysis was employed. The data were collected from the Kegemaranku textbook and analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing, based on the BSNP (National Education Standards Agency) textbook assessment guidelines. Results: The analysis revealed that the textbook achieved high feasibility scores: 94.79% for conformity with student development, 92.70% for communicativeness, and 96.35% for the alignment and integration of thought flow. These results categorize the textbook as "very feasible" across all assessed dimensions, although minor inconsistencies were found in explaining abstract concepts and applying Indonesian language rules in certain sub-themes. Implication: The findings suggest that the textbook can effectively support Grade 1 students’ cognitive, social-emotional, and language development. However, continual monitoring and refinement are recommended to ensure even higher linguistic clarity and developmental alignment, which are critical for achieving curriculum goals. Novelty: This study offers a comprehensive and specific evaluation of language feasibility in early grade textbooks by integrating indicators of communicative clarity and developmental appropriateness based on the 2013 Curriculum. It highlights the need for systematic textbook reviews even for materials officially endorsed by national education authorities.